Brideshead revisited : the sacred and profane memories of Captain Charles Ryder, a novel - Waugh, Evelyn, 1903-1966 (Little, Brown, 1945)
Captain Charles Ryder, stationed at Brideshead, recalls his boyhood associations with the odd but charming members of an English noble family. The story of Charles Ryder and his involvement with an aristocratic Roman Catholic English family, the Marchmains.